Use of a homemade introducer guide (bougie) for intubation in emergency situation in patients who present with difficult airway: a case series - Dexheimer Neto,Felippe Leopoldo (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: The incidence of difficult airway reaches 10% of emergency intubations. Although few studies address the use of handmade introducer guides in emergency and intensive care environment, there are descriptions of handmade guides available on the Internet. We describe a case series on the use of a handmade introducer guide (bougie) for emergency intubation in patients with difficult airway. CASE REPORT: The handmade introducer guide was used in five consecutive patients with difficult airways, and clinical instability and in the absence of another immediate method to obtain an airway. This technique provided successful intubation and there were no complications. CONCLUSIONS: The use of the handmade introducer guide can be a useful option for the management of difficult airways.